Titanium oxide coating and acid etching on platelet activation in dental implants - Maharani, Adella Syvia; Ismiyati, Titik; Aditama, Pramudya; Abdullah, Johari Yap; Aziz, Ihwanul (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Titanium is the most widely used dental implant material, but it requires surface treatment to improve osseointegration. While coating implants with TiO2, residue can arise, which may lead to contamination. To address this, 10% HF etching is added. This study investigated the effect of TiO2 coating using sputtering and HF etching on platelet activation in titanium dental implants. Laboratory experiments were conducted on titanium implants (Ø = 4 mm; length = 12 mm) treated with TiO2 coating and 10% HF etching. Twenty-four samples were divided into four groups (n = 6): Group I (TiO2), Group II (TiO2 + HF 5 min), Group III (TiO2 + HF 10 min), and Group IV (TiO2 + HF 20 min). Platelet activation was assessed using CD41 and CD62P expression markers. Data analysis employed one-way ANOVA and post hoc LSD test (p = 0.05). Platelet activation ranged from 20.31 ± 1.78% to 35.90 ± 3.81%. One-way ANOVA revealed a significant effect (p < 0.05) of both TiO2 coating and acid etching on activation. LSD post hoc test showed significant differences (p < 0.05) between all groups except for the 10 and 20-minute etching periods. TiO2 coating with 10 minutes of HF etching resulted in the optimal activation level.